Program Aplikasi Pengelolaan Persediaan Barang Habis Pakai Berbasis Web pada Unit Pelayanan Pendapatan Daerah Kota Banjarbaru - Nadia Puteri Utami; Muhammad Bahit; Tiara Regita Cahyani (Akuntansi, 2024)
Office stationery (ATK) is office equipment that plays a vital role in the running of the company's administrative functions. ATK will generally be restocked periodically when the inventory has run out, so that office stationery can be categorized as consumables. The system for recording inventory of consumables at the Banjarbaru City Regional Revenue Service Unit is carried out manually and computerized. However, there are still many features that are not available in the computer system and especially the issuance of goods is still done manually. Based on the facts in the field, this can trigger problems that can occur due to the recording of consumable goods inventory which is still done manually, namely the physical entry and exit of goods cannot be known periodically and does not rule out the possibility of damage or loss of books containing records of goods expenditure. This problem is the basis for researchers to take the research topic of inventory management of consumables in the form of office stationery at the Banjarbaru City Regional Revenue Service Unit. This research method uses a descriptive qualitative research method with a case study approach. Data information is obtained through observation, interviews, and direct documentation on the object of research. The types of data used are qualitative data and quantitative data. The results of this study are a web-based consumable inventory management application program using PHP and MySQL which is needed by the Banjarbaru City Regional Revenue Service Unit and several constructive suggestions in the hope that the current system will be more effective and efficient.